Xeroderma Pigmentosum: Sedimentation and Cell Survival Studies Following Ionizing Radiation - Campbell, Margaret G. (My University, 1972)
In spite of the difficulties involved in molecular and cellular studies of antibiotic-free cultures of primary human cells, investigations of the sedimentation and survival properties of cell cultures derived from Xeroderma Pigmentosum patients were successfully carried out. Emphasis was on the cellular and molecular effects of ionizing radiation; however preliminary data for cell survival after exposure to UV was obtained.
Keywords: molecular, cellular, ionizing, radiation, sedimentation, pigmentosum